b+3+b=b+50

Simple and best practice solution for b+3+b=b+50 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b+3+b=b+50 equation:


Simplifying
b + 3 + b = b + 50

Reorder the terms:
3 + b + b = b + 50

Combine like terms: b + b = 2b
3 + 2b = b + 50

Reorder the terms:
3 + 2b = 50 + b

Solving
3 + 2b = 50 + b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-1b' to each side of the equation.
3 + 2b + -1b = 50 + b + -1b

Combine like terms: 2b + -1b = 1b
3 + 1b = 50 + b + -1b

Combine like terms: b + -1b = 0
3 + 1b = 50 + 0
3 + 1b = 50

Add '-3' to each side of the equation.
3 + -3 + 1b = 50 + -3

Combine like terms: 3 + -3 = 0
0 + 1b = 50 + -3
1b = 50 + -3

Combine like terms: 50 + -3 = 47
1b = 47

Divide each side by '1'.
b = 47

Simplifying
b = 47

See similar equations:

| ly-8l+6=15 | | 3a+1=a+19 | | 15.08+w=30.08 | | Cosx/cos^2(2x) | | -5x-3*-13=30 | | 7m+48=8(m+7) | | 3b^2+11b+8=0 | | -5x-(3*-13)=30 | | 18=5-2+6x-x | | -(x-8)+4=2(7)+x | | x+14=35 | | (r-p)/(x-q)=m | | -5x-(-3*-13)=30 | | 2x-4-6=0 | | 12+[6+(13-7)]2-5= | | 72/4.8=20.4/c | | -(x-8)+4=2(-1)+x | | y+4.3=5.9 | | 42x^2-40x+8=0 | | 5k^2+35k+60=0 | | -(x-8)+4=2(1.25)+x | | 12/x=7/3 | | -(x-8)+4=2(0)+x | | 3(2p+7)=1 | | 7/n=24.5/56 | | 7(1-5r)+6r=94 | | 6(9x+2)=54x-7 | | X/9=7/5 | | -(x-8)+4=2(-5.7)+x | | a(ax-a)+6(x+6)=0 | | x^2-5y^2-4x+4y-6=-6y^2-6y+10x-64 | | 84/x=8 |

Equations solver categories